2013
DOI: 10.1002/bit.24993
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of Saccharomyces cerevisiae for the production of 2‐phenylethanol via Ehrlich pathway

Abstract: 2-Phenylethanol (2-PE), a fragrance compound with a rose-like odor, is widely used in perfumery and cosmetics. Here, we report the first metabolic engineering approach for 2-PE production in Saccharomyces cerevisiae. 2-PE can be produced from the catabolism of L-phenylalanine via Ehrlich pathway, consisting of transamination to phenylpyruvate by Aro9, decarboxylation to phenylacetaldehyde by Aro10, and reduction to 2-PE by alcohol dehydrogenases. We demonstrated that Ald3 is mainly responsible for phenylacetal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
109
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(113 citation statements)
references
References 32 publications
1
109
1
Order By: Relevance
“…Kim et al [11] also reported enhanced 2-PE production in S. cerevisiae using metabolic engineering approach. The engineered strain with ALD3 deletion and over-expressing ARO9, ARO10, and the transcription factor Aro80 produced 4.8 g L -1 2-PE in a batch culture system.…”
Section: -Pe Production In Recombinant Strainsmentioning
confidence: 91%
“…Kim et al [11] also reported enhanced 2-PE production in S. cerevisiae using metabolic engineering approach. The engineered strain with ALD3 deletion and over-expressing ARO9, ARO10, and the transcription factor Aro80 produced 4.8 g L -1 2-PE in a batch culture system.…”
Section: -Pe Production In Recombinant Strainsmentioning
confidence: 91%
“…Although several BAHDs acyltransferases similar to BPBT have been shown to transfer benzoyl-CoA onto 2-phenylethanol [65, 66], the use of hydoxycinnamoyl-CoA donors (e.g., caffeoyl-CoA) by these enzymes has never been reported and could enable the biological synthesis of valuable hydroxycinnamate phenethyl esters. Taking advantage of existing engineering strategies that yield high titers of alcohols and 2-phenylethanol should enable the economical synthesis of benzoate alcohol esters and CAPE in yeast [67, 68].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…This includes its deamination, decarboxylation and reduction that are conducted by ARO9, ARO10 and various alcohol dehydrogenases (ALD1-5) in S. cerevisiae respectively. Metabolic engineering efforts to increase 2-PE levels included the streamlining the Ehrlich pathway which involved the overexpression of ARO9 and ARO10 with the concomitant removal of a competing phenylacetaldehyde oxidase (ALD3) [39]. A transcription factor (ARO80) is known as an activator of the ARO9 and ARO10 genes and its overexpression, together with ARO9 and ARO10, led to a four-fold increase in 2-PE levels.…”
Section: Phenylpropanoidsmentioning
confidence: 99%